The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1063/1.3122926
|View full text |Cite
|
Sign up to set email alerts
|

Pre-edges in oxygen (1s) x-ray absorption spectra: A spectral indicator for electron hole depletion and transport blocking in iron perovskites

Abstract: The e g ↑ / ͑t 2g ↓ + e g ↓͒ band ratio in cation-substituted La-Fe oxides is identified in O ͑1s͒ x-ray absorption spectra as a linear spectral indicator for conducting electron holes. The t 2g ↓ and e g ↓ bands act as a conductivity inhibitor by ferromagnetic double exchange coupling on the e g ↑ electron. Disorder induced by substitution appears to modulate the hole conduction such that an exponential relation is found between the conductivity and the e g ↑ / ͑t 2g ↓ + e g ↓͒ ratio and hole concentration. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…represent the unoccupied oxygen 2p orbitals and also reflect the empty Fe/Ni 3d bands at the pre-edge (524 eV -527 eV). The triplet at around 525 eV can be attributed to bands of e g (↑), t 2g (↓) and e g (↓) bands [21]. Comparing the pre-edge region of the spectra shown in Figure 6, we can easily identify that the intensity of e g (↑) peak increases with increasing Sr content in the samples.…”
Section: Oxygen K Edgementioning
confidence: 75%
“…represent the unoccupied oxygen 2p orbitals and also reflect the empty Fe/Ni 3d bands at the pre-edge (524 eV -527 eV). The triplet at around 525 eV can be attributed to bands of e g (↑), t 2g (↓) and e g (↓) bands [21]. Comparing the pre-edge region of the spectra shown in Figure 6, we can easily identify that the intensity of e g (↑) peak increases with increasing Sr content in the samples.…”
Section: Oxygen K Edgementioning
confidence: 75%
“…We begin this discussion with an example from solid oxide fuel cell cathodes, which are typically built from metal oxides with ABO 3 Experimental spectroscopic evidence is then provided in the oxygen K-shell X-ray absorption spectra, which are recorded with X-ray energy of around 520-560 eV. Whereas the LaFeO 3 with Fe 3+ has in the pre-edge a nice e g -t 2g doublet, the substituted compound with a portion of Fe 4+ shows an additional peak in the NEXAFS spectra, representative of the electron hole, L. It has been shown that the relative spectral weight of this hole peak scales exponentially with the electronic conductivity of the compound [60,61].…”
Section: Characterization Of Metal Oxidesmentioning
confidence: 99%
“…High temperature oxidation and reduction studies [34] and catalysis studies [36] have also been made recently with in-situ or operando sulphur XAS, for example. Sulphur as the ligand ion is also of interest in connection with metal ions [37] and could in future studies open up new opportunities for the understanding and quantification of electronic transport processes in SOFC anodes, where newly formed NieS compounds are subject to exchange interactions, in analogy to 3d metal oxides at SOFC cathodes, for example [38,39]. Latter would constitute an extension of sulphur XAS from molecular structure and chemical speciation of sulphur motifs towards electronic structure, valence band and electronic transport properties of aged SOFC anodes.…”
Section: Motivation and Goalmentioning
confidence: 99%